The emergence of portable private-personal territory: Smartphones, social conduct and public spaces. (August 2016) - Hatuka, Tali; Toch, Eran
This paper underscores the centrality of individual technological devices, particularly mobile phones, in structuring contemporary social interaction in public spaces. It illustrates the need to re-think the relationship between information and communications technologies and practices of sociability in public spaces. Based on surveys of users of mobile phones (basic mobile phones and smartphones), we explore the practices and actions of subjects in public spaces. Empirical analysis shows that the use of mobile phones and, particularly, smartphones, is gradually modifying the normative constraints associated with place and social codes, simultaneously enhancing both a sense of freedom and estrangement. Based on our findings, the paper suggests the concept of portable private-personal territory to better understand the personal space individuals develop with the support of technology. Finally, the paper concludes with a reflection on the future implications of portable private-personal territories for public spaces and cities.